An organoid-based carcinogenesis model induced by in vitro chemical treatment. (12th February 2020) - Naruse, Mie; Masui, Ryoichi; Ochiai, Masako; Maru, Yoshiaki; Hippo, Yoshitaka; Imai, Toshio
Abstract: Animal carcinogenesis models induced by environmental chemicals have been widely used for basic and applied cancer research. However, establishment of in vitro or ex vivo models is essential for molecular mechanistic elucidation of early events in carcinogenesis, leading to clarification of the total mode of action. In the present study, to establish an organoid-based chemical carcinogenesis model, mouse organoids were treated in vitro with 4 genotoxic chemicals, e.g. ethyl methanesulfonate (EMS), acrylamide (AA), diethylnitrosamine (DEN) and 7, 12-dimethylbenz[ a ]anthracene (DMBA) to examine their tumorigenicity after injection to nude mice. The four chemicals were reported to induce lung, liver or mammary carcinomas in mouse models. DMBA-treated mammary tissue-derived organoids with Trp53 heterozygous knockout exhibited tumorigenicity, but not those with wild-type Trp53, reflecting previous reports of corresponding animal models. Treatment of lung organoids with or without Trp53 knockout with EMS or AA resulted in carcinogenic histopathological characteristics, and the activation of oncogenic kinases was demonstrated in the nodules from the nude mouse subcutis. DEN-treated liver (biliary tract) organoids also had an increased number of similar changes. In conclusion, an ex vivo model for chemical carcinogenesis was established using normal mouse tissue-derived organoids. This model will be applied to detect early molecular events, leading to clarification of the mode of action of chemical carcinogenesis.